Designing Enterprise Architecture of The Smart Governance of Bogor - Rachmat Rachmat (Jurnal Sistem Informasi, 2019)
Bogor City is one of the one hundred selected cities which are expected to implement Smart City. One component to realize Smart City is the implementation of e-government through the use of Information Technology (IT) through the Smart Governance dimension which is expected to be able to harmonize the implementation of the Bogor ICT integration strategy with the existing ICT masterplans. Based on this case, this study was aimed to make an application of the Enterprise Architecture framework to support the Smart City Masterplan in Bogor City. In addition, a comprehensive analysis of the current ICT conditions, gap analysis, and future targets for Bogor was carried out in this study. The data and information used in this study came from interviews with stakeholders in the Local Government Organization of Bogor, related documents, and information downloaded via the official sites of the Bogor city government. The method applied in this study was TOGAF ADM to design the Bogor Enterprise Architecture framework. The study provides recommendations for the design of Smart Governance Enterprise in the City of Bogor. In addition, based on the results of a gap analysis of business architecture, information systems and, technology, the need for an integrated system, interoperability, budget amount, ICT human resources, and ICT infrastructure needs to be improved, as well as the need for regulations and standards to protect Bogor City e-government products.